Harmonizing Investigative Powers of KPK and Tax Authority in State Financial Crimes - Vito Oktovianus Maupiku; Mardian Putra Frans (JUSTISI, 2025)
This study aims to analyze the overlap of investigative authority between investigators of the Corruption Eradication Commission (KPK) and investigators of the Directorate General of Taxes (DJP) in criminal acts that cause financial losses to the state and to harmonize these authorities.The study is a normative legal study using a legislative approach and a conceptual approach.Novelty previous studies have discussed the legal analysis of the authority of the Corruption Eradication Commission as the prosecutor of corruption offenders and the position of civil servant investigators of the Directorate General of Taxes in the framework of criminal tax law enforcement in Indonesia. The difference in this study is that it identifies and analyzes in depth the potential overlap of authority between the DJP investigators and the KPK in handling cases involving tax crimes that have implications for state financial losses, as well as formulating a model for coordination and synchronization of authority based on the principles of ultimum remedium and efficiency of law enforcement based on the principles of limited authority and lex specialis systematis.The results the application of the principle of limited authority and the principle of lex specialis systematis strengthens the authority of DJP investigators in handling tax crimes that cause financial losses to the state.Conclusion investigators of the DJP have more specific and effective authority in handling tax crimes that cause financial losses to the state, based on the principle of limited authority and the principle of lex specialis systematis.